Takhrīj al-Hadīṡ Digital: Metode Ekstraksi Sanad-Matan dari Naskah Klasik Berbasis Corpus Terstruktur - Sari, Aulia Permata; Rizki, Miladur; Saragih, Anisah Ramadhani; Siregar, Idris; Al-Fikri, Hafiz (Nizamiyah: Jurnal Sains, Sosial dan Multidisiplin, 2025)
The development of digital hadith studies demands methodological updates in the practice of takhrīj al-Ḥadīṡ, especially when dealing with a large-scale, multi-layered, and editorially heterogeneous corpus of classical hadith texts. Conventional takhrīj approaches that rely on manual book searches and thematic indexes show limitations in efficiency, consistency, and the ability to systematically manage the complexity of sanad and matan variations. This study aims to develop and test a digital takhrīj al-Ḥadīṡ method through structured corpus-based sanad–matan extraction compiled from classical hadith manuscripts. The research method uses a qualitative-analytical approach with the integration of digital text processing on a curated hadith corpus, including the stages of text normalization, sanad–matn segmentation, mapping of narrator relationships, and verification of transmission patterns based on the rules of hadith science. The results show that the developed method can reconstruct the sanad–matn structure more explicitly and consistently, identify the boundaries of sanad and matan with a high degree of accuracy, and trace variations in editorial and transmission paths comparatively across sources. Digital extraction demonstrates its effectiveness in accelerating the takhrīj process, reducing data redundancy, and improving the traceability of sanads without violating the basic principles of hadith criticism. The level of conformity of digital methods with the principles of hadith science is reflected in its ability to maintain the hierarchy of narrators, continuity of transmission, and differentiation of matan redactions. Implicatively, this study confirms the methodological contribution of digital takhrīj al-Ḥadīṡ as a complementary approach that broadens the horizon of contemporary hadith analysis, strengthens research accuracy, and opens up opportunities for the integration of hadith science with digital corpus studies more systematically and sustainably.